PRAKTEK JUAL BELI “SEROK LIVE” TIK TOK SHOP DALAM TINJAUAN EKONOMI ISLAM - Syamratun Nurjannah; Reni Helvira; Ari Widiati (Faculty of Islamic Economics and Business, 2023)
This study discusses the Practice of Serok Live Buying and Selling Islamic Economics’ Review. Buying and selling are generally defined as the process of exchanging goods or services between sellers and buyers. Along with the developing era, they were marked by many changes in various aspects of life, from manual to application. The same things happened for buying and selling activities. TikTok is an application used to create and share different short recordings within a vertical organization. As technology develops, TikTok issued two features which are used in buying and selling, such as the Tiktok shop and buying and selling via Live Streaming. The purpose of this research is to find out the practice of buying and selling using the TikTok shop